(untitled) (Physical Culture and Sport: Scientific Perspective, 2023)
The article examines the patterns of regulation of mental states, which can be a significant help in solving many tactical and strategic tasks of sports activities. The purposed - the development of a system of psychological and pedagogical techniques for correcting pre-start emotional states of young martial artists. Male wrestlers aged from 18 to 24 were examined. For the solution of the set tasks was used to compare two groups: − 40 people (20 athletes from freestyle wrestling, and 20 karate athletes). Set tasks were solved using the following research methods: analysis of scientific and methodical literature; pedagogical experiment; survey; methods of mathematical statistics. Developed the system of psychological and pedagogical methods of optimization of prestart emotional states consisted of four blocks: block A (heterotraining, neuromuscular relaxation, autotraining); 2) block B (ideomotor training, adapted version of hypnoideomotor training, sensitization); 3) block C (programming for success in sports, self-programming for success in sports using audio and video recordings; 4) block D (balancing the processes of activation and inhibition of the central nervous system). According to the results of the study, it was found that the improvement in mental reliability occurred to a greater extent in athletes who were engaged in freestyle wrestling in terms of competitive emotional stability (by 3,33 points) and the motivational and energy component (by 3,08 points). Improving of strong-willed qualities occurred to a greater extent in athletes who were engaged in freestyle wrestling in terms of purposefulness (by 6,80 points); self-control in athletes who were engaged in karate improved by 5,58 points. As a result of the experiment, the effectiveness of the proposed method "System of psychological-pedagogical techniques for correcting the pre-start emotional states of martial arts athletes" was proven, its positive effect on both the mental state of athletes and training-preparatory and competitive activities in general on the basis of which we can recommend implementation of this system in the work of sports groups.